STRATEGI PENGEMBANGAN JAGUNG HIBRIDA KELOMPOK TANI DERMAWAN DI DESA PESAKU KECAMATAN DOLO BARAT KABUPATEN SIGI - Rahmi, Ainun; Sulaeman, Sulaeman; Malik, Shintami M (Fakultas Pertanian, Universitas Tadulako, 2024)
This research was conducted at the Dermawan Hybrid Corn Farmers Group located in Pesaku Village, Dolo Subdistrict, Sigi District. The selection of this location was purposive, aligning with the research objectives. The study's respondents included eight individuals, comprising both internal and external stakeholders. The internal respondents consisted of the group leader, treasurer, secretary, and one member of the Dermawan Farmers Group. The external respondents included two partners who served as part of the production monitoring team and two regular consumers of the group's produce. The study employed strategy formulation analysis tools, including the Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, Internal-External (IE) matrix, and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The analysis of the agribusiness development strategy for hybrid corn farming within the Dermawan Farmers Group identified key internal factors, notably strengths and opportunities. The SWOT analysis resulted in the identification of three strategic approaches for further development.